Use of Anakinra in Patients with Cryopyrin-Associated Periodic Syndromes and Other Autoinflammatory Diseases - Mikhail M. Kostik ("Paediatrician" Publishers LLC, 2016)
The article describes the main autoinflammatory syndromes as well as the key role of interleukin (IL) 1 in the pathogenesis of these diseases. It also presents the data on the experience of anakinra using (soluble IL-1 receptor antagonist) as well as the results of randomized clinical trials and descriptions of anakinra use case series in autoinflammatory and a number of other non-rheumatic diseases. The data on the efficacy and safety of a soluble IL-1 receptor antagonist is given.